The Impact of Knowledge About Business Model Canvas (BMC) on Entrepreneurial Interest of Young Generation in Jabodetabek - Hendrasto, Nur; Chairiyati, Fauziah; Haidar, Abdullah; Herindar, Evania; Rehman, Hafiz Mudassir (Indonesian Journal of Business and Entrepreneurship, 2024)
This research aims to investigate the influence of Business Model Canvas (BMC) knowledge on entrepreneurial knowledge among young generations in the Jabodetabek region. There is a growing need to understand the role of BMC in stimulating entrepreneurial interest among the youth. This study seeks to provide insight to the younger generation on the importance of entrepreneurship and to encourage the development of an entrepreneurial interest through the application of the Business Model Canvas (BMC) learning method. The research employs purposive sampling techniques for data collection and utilizes a quantitative approach with simple regression analysis.The data reveals a correlation coefficient (R) of 0.65 or 65%, with a coefficient of determination (R Square) of 0.423. Data processing using SPSS 29 indicates an F value of 60.878 with a significance level of 0.001 < 0.05. Partial significance test (t-test) shows that the Entrepreneurial Knowledge BMC variable attains a t value of 7.802, exceeding the critical t-table value of 1.992, with a significance value of 0.0005, smaller than 0.05. These findings indicate a positive and significant relationship between BMC knowledge and entrepreneurial aspirations among young individuals in Jabodetabek. Entrepreneurial knowledge through BMC has a positive and significant impact on entrepreneurial interest. Therefore, enhancing entrepreneurial knowledge acquired through BMC has the potential to increase entrepreneurial interest among the younger generation. Keywords: BMC knowledge, business model canvas, young generation, entrepreneurial interest